Online Loans: A Solution or a Problem? Perspectives on Education and Society - Rosadi, Rama (International Journal of Public Administration and Policy, 2025)
The phenomenon of online loans, as one of the innovations in financial technology, has significantly impacted society, particularly younger generations, by offering quick and easy access to finances. This study aims to analyse the effects of online loans on financial literacy, social awareness, and character education, while also identifying educational measures to mitigate their negative impacts. Using a descriptive qualitative approach and thematic analysis, this research explores various aspects of individual behaviour related to online loans based on literature and previous studies. The findings reveal that university students are among the groups most vulnerable to consumptive behaviour due to low financial literacy. Furthermore, aggressive debt collection methods often impact users' mental health. The study underscores the importance of incorporating financial literacy into formal education systems as a mitigation strategy, and supports an interdisciplinary approach that integrates digital and financial literacy. The primary conclusion of this research is the need for stricter regulations and more comprehensive education to create a society that uses financial technology wisely. This study contributes to policy development and educational practices in the digital era to mitigate the negative impacts of online loans.